Dampak Program Pemberdayaan Masyarakat Melalui Eco Enzim di Desa Garagata Kabupaten Tabalong - Muhammad Agrianto Suwandi; Setia Budhi (Huma: Jurnal Sosiologi, 2023)
The lack of quality Human Resources often causes social and environmental problems, so that it requires community empowerment, one of which is eco enzymes program. The purpose of this study was to determine the impact of the community empowerment program through eco enzymes on the people of Garagata Village, Tabalong Regency. The research approach used is a qualitative approach with a descriptive type. Data was collected through observation, interviews and documentation. The results of this study indicate that the impact is seen through several aspects, such as institutional improvements through the movement of farmer groups, business improvements to production quality, income improvements through thrifty attitudes, improvements to the physical and social environment that are manifested through environmental cleanliness and increased social relations, improvement life marked by income and environmental improvements, community improvements manifested by improved lives. The community empowerment program through eco enzymes is realized through the enabling stage or the introduction of eco enzymes to the Garagata Village community. Activities carried out such as holding socialization and carrying out social actions. The next stage is efforts to change people's conditions for the better or empowering efforts through training in making eco enzymes. The goal is that people have the ability to make eco enzymes independently. The drawbacks of the community empowerment program through eco enzymes in Garagata Village are not reaching the protecting stage, which is an effort to strengthen the effect of eco enzymes from the effects of using chemical drugs in agriculture.